2012
DOI: 10.4314/ajcem.v13i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Topical Silver Nitrate and Intramuscular Antimonial Drugs in the Treatment of Cutaneous Leishmaniasis in Sokoto, Nigeria

Abstract: Background: Cutaneous leishmaniasis (CL) is a disease of public health importance in Nigeria, with high prevalence in the Northwest and Northeastern part of the country. The side effects of antimonial drugs {stibogluconate (SSG) and meglumine antimoniate} in the treatment of CL have often resulted in poor drug adherence and default by patients and possible drug resistance. The increasing default to follow-up and the significant side effects associated with antimonial therapy necessitated the dire need of alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Regarding to age groups, the results of present study showed high significant differences (P<0.05) in distribution of infection within age groups. The age group 0-10 had the highest infection rate 29 (46.8%) followed by the age group 11-20 represented 14 (22.9%) while the lowest infection found in 51-60 age group 18 (2.4%), as showed in Table (2). The results of this investigation in agreement with [14] who indicated that the high rate of infections was in age group under 12 years.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding to age groups, the results of present study showed high significant differences (P<0.05) in distribution of infection within age groups. The age group 0-10 had the highest infection rate 29 (46.8%) followed by the age group 11-20 represented 14 (22.9%) while the lowest infection found in 51-60 age group 18 (2.4%), as showed in Table (2). The results of this investigation in agreement with [14] who indicated that the high rate of infections was in age group under 12 years.…”
Section: Resultssupporting
confidence: 86%
“…Leishmania spp. which including Leishmania major, Leishmania tropica, and Leishmania aethiopica in old world and Leishmania amazonensis and Leishmania mexicana responsible for infection with CL [2]. Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main types of leishmaniasis: cutaneous leishmaniasis (CL) caused by Leishmania tropica, L. mexicana and L. major. Visceral leishmaniasis (VL) caused by L. donovani and L. infantum and mucocutaneous leishmaniasis (MCL) caused by L. braziliensis (Igbineweka et al, 2012). Cutaneous Leishmaniasis is caused by different species of Leishmania with a specific inclination of each species to a particular geographical region.…”
Section: Introductionmentioning
confidence: 99%